Uji Beberapa Varietas Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Terhadap Lama Cekaman Genangan Air - Situmorang, Amri Ayu; Tabrani, Gunawan; Islan, Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to get the oil palm seedlings variety that were more tolerant to waterlogging stress duration. Research does in the experiments were undertaken at the Agriculture Faculty Station of Riau University from April to June 2016. Experiment done in the completely randomized design 3 x 3. The first factor was the Tenera varieties palm oil seedlings: AA-DP TOPAZ 1 (v1), Sungai Pancur I (v2) and DxP Simalungun (v3). The second factor was waterlogging stress duration: 30 days (g0), 50 days (g1) and 70 days (g3). Variables observed consisted of: seedling height, leaf midrib, stem diameter, canopy root ratio, seedling quality index and seedling dry weight. The results showed that, interaction between the varieties palm oil seedling with waterlogging stress duration was not significant. Effect of waterlogging stress duration take on all observed variables, but the varieties affects to height, number of leaves and dry weight of seedling. The varieties of oil palm seedlings more tolerant to 70 days waterlogging stress duration, compared 30 days or 50 days. The growth of Sungai Pancur I and DxP Simalungun palm oil seedling were better than AA-DP TOPAZ 1. Keywords: Tenera varieties palm oil seedling, waterlogging stress duration.